Privacy in the Age of Big Data: Recognizing Threats, Defending Your Rights, and Protecting Your Family - Payton, Theresa; Claypoole, Ted (Rowman & Littlefield Publishers, 2023)
A thorough update to a classic in the field of privacy and big data. We have a global privacy problem. The average person provides more information about themselves to more outsiders than any time in history. Corporations, governments and even our neighbors can know where we are at times, can quickly learn our preferences and priorities and see who we meet. The past decade has brought deep changes in the collection of our private information, the regulation of that collection, and in people’s sensitivity to loss of privacy. The nascent privacy-threatening technology trends of a decade ago have blossomed into relentless data-capturing systems that police and companies have come to rely on. To address the expansion of personal data capture, entire data regulatory regimes have arisen throughout the world, with new regulations added each year. People are more concerned, regulators are more aggressive, yet data collection continues to increase with consequences around the world. Social media use has fragmented in the past five years, spreading personal information over dozens of platforms. Even most of our new televisions have started collecting second-by-second information about our households recently, and some of those televisions can recognize the individuals watching and the devices they carry. Amazon just activated a new worldwide network using bandwidth from personal wifi of Echo devices and Ring security systems. The beat of new intrusions never seems to end. These data trends are relentless, and yet response to the pandemic accelerated them. Rapid development of “contactless everything” became the norm. Contact tracing apps became acceptable. QR codes for everything from menus to contact information were created quickly. Businesses are faced with hybrid in office and remote workforces. More people are dependent on online and mobile technologies for food, medicine, and even human connection. And each of these contacts can be captured somewhere and logged in a file for marketing or surveillance. People want to keep their lives private, but they don’t know how. The second edition of Privacy in the Age of Big Data addresses the significant advances in data-driven technology, their intrusion deeper in our lives, the limits on data collection newly required by governments in North America and Europe, and the new security challenges of world rife with ransomware and hacking. This thoroughly updated edition demonstrates personal privacy vulnerabilities and shows ways to live a safer, more private life. Other privacy books tend to focus deeply on the evils of large tech companies or more academic and technical concerns. But Privacy in the Age of Big Data, second edition, helps regular people understand the privacy threats and vulnerabilities in their daily lives and will provide solutions for maintaining better privacy while enjoying a modern life. Unlike other books, this one shows what you can do to make a difference to understand your current digital footprint and what you need to do to claw back your privacy and secure it in the future. While PRIVACY IN THE AGE OF BIG DATA will have cross-sectional appeal to many demographics, working adults 25-60 and CEOs and Boards of businesses are the primary demographic--young enough to know we need to do something to protect privacy and old enough to remember what happens when we haven’t in the past. With down-to-earth prose and examples pulled from daily life, the writing style will attract buyers of all education levels.